Modern problems of family research and family suport - Kantowicz, Ewa (Problemy społeczne: Trwałość i zmienność w dynamicznej rzeczywistości. Księga jubileuszowa z okazji 45-lecia pracy naukowej i dydaktycznej Profesor Jolanty Grotowskiej-Leder, 2022)
Research in recent decades has shown the complexity of the family’s problems and the risks involved in fulfilling its tasks, existential and communication difficulties in families, as well as the unsatisfactory protection of the family, particularly those facing many problems, as well as the imperfection of the family support system. These dilemmas inspire many social researchers, and the family becomes the center of interest of politicians and many representatives of the helping professions. This article discusses the theoretical and methodological aspects of the study and analysis of the issues of the modern family, as well as the practical dilemmas of protecting it and creating a more effective family support system. The author, conducting a summary review of selected social studies on the family, points to theoretical-methodological dilemmas related to the diagnosis and characteristics of the modern family and analyzes examples of legislative solutions as well as actions supporting the family in Poland.